THE EFFECTIVENESS OF THE RADEC LEARNING MODEL ON GRADE IX STUDENTS’ LEARNING OUTCOMES IN SOLID GEOMETRY - Nur Afni; Rahma Nasir; Mustamin Idris; Pathuddin Pathuddin (JME (Journal of Mathematics Education), 2026)
This study aimed to examine the effectiveness of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on the learning outcomes of Grade IX students in solid geometry. The research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The population consisted of ninth-grade students at a junior high school in Palu, and the sample was selected using cluster random sampling. Data were collected through essay-type tests to measure students’ learning outcomes and observation sheets to assess the implementation of the learning model. Data analysis was conducted using the independent sample t-test and N-Gain analysis at a significance level of 0.05. The results showed that the Sig. (2-tailed) value was 0.001, indicating a statistically significant difference in learning outcomes between the experimental and control classes. The average N-Gain score in the experimental class was 0.56, which falls into the moderate category and is higher than that of the control class. These findings indicate that the RADEC learning model is effective in improving students’ learning outcomes in solid geometry and can serve as an alternative instructional approach in mathematics education.